The IMPLEMENTATION OF THE HOPE FAMILY PROGRAM IN INCREASING COMMUNITY WELFARE IN SHARIA ECONOMIC PERSPECTIVE: IMPLEMENTATION OF THE HOPE FAMILY PROGRAM IN INCREASING COMMUNITY WELFARE IN SHARIA ECONOMIC PERSPECTIVE - Safitri Fitri, Yuliana; Ramli, Fauzan; Mawaddah, Fadila (Pusat Kajian Berkelanjutan UIN Sulthan Thaha Saifuddin Jambi, 2023)
The Family Hope Program is a social protection program that provides non-cash assistance to poor families designated as Beneficiary Families. The Family Hope Program is a program based on poor families, so the main targets are economically disadvantaged families. The Family Hope Program is an effort directed towards the formation and human resources focus on aspects of education, health, and social welfare. This research is entitled